2015
DOI: 10.1016/j.biortech.2015.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hazardous events on the removal of nutrients and trace organic contaminants by an anoxic–aerobic membrane bioreactor receiving real wastewater

Abstract: The impacts of four simulated hazardous events, namely, aeration failure, power loss, and chemical shocks (ammonia or bleach) on the performance of an anoxic-aerobic membrane bioreactor (MBR) receiving real wastewater were investigated. Hazardous events could alter pH and/or oxidation reduction potential of the mixed liquor and inhibit biomass growth, thus affecting the removal of bulk organics, nutrients and trace organic contaminants (TrOC). Chemical shocks generally exerted greater impact on MBR performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Specific groups of TrOCs that are poorly degraded by the activated sludge accumulate within the bioreactor of HR-MBR. Sorption on activated sludge contributes to improvement of overall aqueous phase removal of TrOCs in conventional MBRs (Lay et al 2012, Mascolo et al 2010, Phan et al 2015a, Phan et al 2015b, Stevens-Garmon et al 2011. For instance, halogenated TrOCs are widely reported to be persistent to microbial degradation.…”
Section: Effect Of Troc Molecular Structurementioning
confidence: 99%
“…Specific groups of TrOCs that are poorly degraded by the activated sludge accumulate within the bioreactor of HR-MBR. Sorption on activated sludge contributes to improvement of overall aqueous phase removal of TrOCs in conventional MBRs (Lay et al 2012, Mascolo et al 2010, Phan et al 2015a, Phan et al 2015b, Stevens-Garmon et al 2011. For instance, halogenated TrOCs are widely reported to be persistent to microbial degradation.…”
Section: Effect Of Troc Molecular Structurementioning
confidence: 99%
“…They reported high removal efficiency (>80-90%) for acetaminophen, ibuprofen, bezafibrate, estrogens (estrone, estradiol, estriol). Phan et al (2015) reported that membrane bioreactor technology can generally achieve high pollutant removal efficiency with the effluent quality largely complying with the Australian guidelines for water recycling (except for caffeine, estrone and triclosan). Performance is a function of temperature (Suárez et al 2012;Gurung et al 2017) and pH-dependent (Sanguanpak et al 2015).…”
Section: Membrane Bioreactor Technology For Emerging Contaminant Removalmentioning
confidence: 73%
“…Research interests in membrane reactor technique have grown rapidly in recent years. Indeed, studies also showed that membrane bioreactors are effective in removing emerging substances, mostly pharmaceuticals (Maeng et al 2013;Ojajuni et al 2015;Phan et al 2015;Sanguanpak et al 2015;Alvarino et al 2017;Besha et al 2017;Gurung et al 2017;Abargues et al 2018;Jiang et al 2018;Ma et al 2018;Mert et al 2018;Bodzek 2019;Borea et al 2019;Monteoliva-García et al 2019;Lim et al 2020;Pathak et al 2020;Racar et al 2020;Vieira et al 2020). Maeng et al (2013) demonstrated that membrane bioreactor technology is an excellent approach for removing trace pharmaceuticals from complex wastewater.…”
Section: Membrane Bioreactor Technology For Emerging Contaminant Removalmentioning
confidence: 99%
“…Research interests in membrane reactor technique have grown rapidly in recent years. Indeed, studies also showed that membrane bioreactors are effective in removing emerging substances, mostly pharmaceuticals (Maeng et al 2013;Ojajuni et al 2015;Phan et al 2015;Sanguanpak et al 2015;Alvarino et al 2017;Besha et al 2017;Gurung et al 2017;Abargues et al 2018;Jiang et al 2018;Ma et al 2018;Mert et al 2018;Bodzek et al 2019;Borea et al 2019;Monteoliva-García et al 2019;Lim et al 2020;Pathak et al 2020;Racar et al 2020;Vieira et al 2020). Maeng et al (2013) demonstrated that membrane bioreactor technology is an excellent approach for removing trace pharmaceuticals from complex wastewater.…”
Section: Membrane Bioreactorsmentioning
confidence: 99%